Sustainability Orientation, Crowdfunding Engegement Motivation, and Crowdfunding Success in Indonesia - Ahmad Junaedi; Christina Whidya Utami; Christian Herdinata (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
The development of the equity crowdfunding ecosystem in Indonesia, focusing on campaign sustainability is seen to increase the chances of fundraising success by increasing investor trust, social legitimacy, and emotional engagement. This study aims to analyze the effect of sustainability orientation on Equity Crowdfunding campaign performance on platforms regulated by Otoritas Jasa Keuangan, and to describe the mediating role of Crowdfunding Engagement Motivation. The approach applied is a systematic conceptual literature review, by searching for references related to sustainability, investor participation, and crowdfunding performance, then compiled through narrative synthesis. The results of the study indicate that campaigns that prioritize environmental and social elements can increase Crowdfunding Engagement Motivation such as individual value encouragement, community support, and mission alignment which ultimately encourage active investor behavior and success in fundraising. Thus, Crowdfunding Engagement Motivation functions as a positive link between sustainability orientation and Equity Crowdfunding outcomes. The practical implication is that entrepreneurs and managers of Equity Crowdfunding platforms in Indonesia should strategically prioritize sustainability values ​​in campaigns to increase investor participation and funding efficiency. This study is not an empirical study, but a conceptual synthesis that explains theoretical pathways and practical strategies in local Equity Crowdfunding.